WHITE COLLAR CRIMES AND EXISTING LEGAL FRAMEWORK IN INDIA - Khan, Mohammad Azvar (National Journal of Criminal Law, 2022)
The criminal justice system of the country provides for criminality in white collar crimes. The mere existence of such laws has a symbolic impact on the society. Though criminal sanctions have been imposed for violation of white collar crimes but the strategy has not worked as a deterrent or a tool for achieving compliance. Both the substance and the picture of policing be lost on the off chance that crook and withdrawn movement isn't perceived, forestalled and indicted .If the society is protected from traditional crimes then people get freedom to heighten their level of social and economic interaction thus enhancing their quality of life and if the society is free from white collar crimes then it adds reliability to this quality. To disregard middle-class wrongdoing is to undermine the trustworthiness of our general public, similarly as we overlook the security of society when we neglect to adapt to normal wrongdoing. Deferring or delaying activity in middle-class violations is a surrender of policing. The High Court once said the nature of a country's civilization can be to a great extent estimated by the strategies it involves in the implementation of criminal regulation.